Negative pressure wound therapy in the treatment of deep sternal wound infections – a critical appraisal. (1st December 2021) - Myllykangas, Heidi-Mari; Berg, Leena T.; Husso, Annastina; Halonen, Jari
Abstract: Introduction . Negative pressure wound therapy (NPWT) has widely become the first-line option in the treatment of deep sternal wound infections. After several positive reports in comparison with conventional treatment, very recent studies comparing NPWT with early reconstruction have favored the latter. Our aim was to evaluate the effectiveness and safety of NPWT in comparison with early flap reconstruction. Materials and methods . We concluded a retrospective analysis of 125 patients with deep sternal wound infection treated in a single institution between the years 2006 and 2018. NPWT became the first-line treatment in our hospital in 2011. The study group consisted of 55 patients treated primarily with NPWT with or without subsequent flap reconstruction. The control group consisted of 60 patients treated with flap reconstruction without prior NPWT. Ten patients with an immediate re-fixation and direct wound closure were excluded. Results . There were no significant differences between the two groups concerning the type or urgency of the original open-heart surgery, age, gender, or co-morbidities. In the NPWT group there was significantly higher mortality ( p = .002), longer stay in the intensive care unit ( p = .028), and in the university hospital ( p < .001) as well as higher number of operations ( p < .001). However, there were somewhat more surgical complications in the control group as well as a higher number of distant flap reconstructions. Overall, five patients suffered from NPWT associated bleeding. Conclusion . Our results raise concerns about the wide use of NPWT as a first-line treatment of deep sternal wound infections. Further evaluative studies are warranted to confirm the results.